1996
DOI: 10.1183/09031936.96.09020274
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with drug-resistant Mycobacterium tuberculosis in Castilla-la-Mancha (Spain)

Abstract: The aim of this study was to investigate the incidence of primary and secondary resistance to antituberculosis drugs and the risk factors associated with the resistance in southeast Spain.Our research was based on the clinical histories of 276 patients, diagnosed as having tuberculosis by positive culture, who were tested for drug susceptibility between January 1988 and October 1994. The clinical histories were checked by two independent investigators. Drug-resistant strains were isolated from 24 patients (8.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
1
7
0
7
Order By: Relevance
“…In Nepal, levels of drug resistance are very high, with nearly 14.7% of new patients resistant to at least one drug 2 Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. [4][5][6][7][8][9][10] The present study also revealed that previous treatment of tuberculosis was strongly associated with MDR TB OR =2.799 (95 % CI 1.159 to 6.667) (p=0.020).According to the National Tuberculosis Programme's Nepal National Survey in 2007, MDR among new cases of TB is 2.9% and MDR among previously treated cases is at 11% thereby giving a ratio of approximately 4:1 for prevalence of MDR in these groups, 2 this pattern holds true in our study too. Lomtadze et.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, levels of drug resistance are very high, with nearly 14.7% of new patients resistant to at least one drug 2 Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. [4][5][6][7][8][9][10] The present study also revealed that previous treatment of tuberculosis was strongly associated with MDR TB OR =2.799 (95 % CI 1.159 to 6.667) (p=0.020).According to the National Tuberculosis Programme's Nepal National Survey in 2007, MDR among new cases of TB is 2.9% and MDR among previously treated cases is at 11% thereby giving a ratio of approximately 4:1 for prevalence of MDR in these groups, 2 this pattern holds true in our study too. Lomtadze et.…”
Section: Discussionmentioning
confidence: 99%
“…Les études montrent des ratios allant de 1,5 à 8 en faveur des hommes [7,[11][12][13][14][17][18][19]. [20,21].…”
Section: Sexeunclassified
“…Plusieurs auteurs ont montré que l'alcoolisme fait partie des facteurs de risque de MDR-TB [12,31]. Les éthyliques seraient généralement inobservants à leurs traitements, ce qui favorise le développement des résistances.…”
Section: Alcoolunclassified
See 1 more Smart Citation
“…During the disease course, higher mortality rate and more frequent side effect to anti-tuberculosis drug are expected. Because of the preexisting liver dysfunction, application of multi-drug combination regimen warrants strict surveillance [62,63].…”
Section: Airways Infectionsmentioning
confidence: 99%